Several audiotapes containing interviews with and a talkshow about Ernst Zündel. Pressconference on Zündel's trial in Munich. Holocaust denial, revisionism - Zündel, Ernst.
Several audiotapes containing interviews with and a talkshow about Ernst Zündel. Pressconference on Zündel's trial in Munich. Holocaust denial, revisionism.